The Effect of Information Technology on Learning (A Study on Civic and Pancasila Education Students at Mataram University) - Sumardi, Lalu; Rispawati, Rispawati; Ismail, M. (Universitas Negeri Malang, 2017)
Abstract: The aim of this research was to know how students completed their academic assignments, the reason why they completed the assignment the way they did, the effects from their choice of approach, and how to solve them. Data collection was done by using documentation, think aloud technique, and focus group discussion. The data analysis was done by using Glaser and Strauss model. The results showed that 91.1% of Civic and Pancasila Education students completed their academic assignments by copying from the Internet. Internal factors consisted of laziness, hedonistic attitude, the tendency to get everything instantly, and lack of awareness about the importance of developing positive mentality and noble character. Meanwhile, external factors consisted of the availability of information on the Internet and the type of task assigned. The effect of such tendency could be categorized into two kinds: short-term and long-term effect. The short-term effect was that the mastery of students’ knowledge was only on the level of “knowing” (C1) and slightly shifted to the level of “understanding” (C2), incomplete and undetailed information about the materials, the materials were not stored in the long term memory, and the students’ way of thinking was not systematic and linear. The long-term effect included the students’ cognitive structure as well as their character which would not be well developed. There were two solutions to address the issue, namely instrumental and mental solution. Instrumental solution included the provision of textbooks, reference books, and the courses’ list of reference books, while mental solution included developing students’ awareness about the importance of scientific way of thinking, building a good attitude and character in everyday’s life, including in the learning process.Keywords: character, cognitive structure, information technology, teaching and learningAbstrak: Tujuan penelitian ini adalah untuk mengetahui bagaimana mahasiswa menyelesaikan tugas akademiknya, alasan mengapa mereka menyelesaikan tugas akademiknya dengan cara-cara tersebut, dampak yang ditimbulkan, dan bagaimana cara mengatasinya. Pengumpulan data dilakukan dengan dokumentasi, think aloud, dan focus group discussion (FGD). Analisis dilakukan dengan model analisis Glaser dan Strauss. Berdasarkan analisis yang dilakukan ditemukan 91,1% mahasiswa Civic Education menyelesaikan tugas akademiknya dengan menyalin-rekat dari internet. Faktor yang menyebabkannya adalah: (1) faktor dari dalam berupa malas, hedonis, instan, dan kurangnya kesadaran tentang pentingnya membangun struktur mental dan karakter yang mulia. (2) faktor dari luar berupa tersedianya semua jenis informasi di internet dan jenis tugas yang diberikan. Dampak yang ditimbulkan adalah (1) dampak jangka pendek, yaitu penguasaan ilmu mahasiswa hanya pada level mengetahui (C1) dan sedikit bergerak ke level memahami (C2), pemahamannya tidak lengkap dan detail, materi tidak terdorong masuk dalam long terms memory, cara berpikir tidak linear dan sistematis dan (2) dampak jangka panjang, yaitu struktur mental mahasiswa tidak berkembang secara lengkap dan sikap mental berkembang kurang baik. Ada dua solusi yang dapat dilakukan untuk mengatasi masalah tersebut, yaitu (1) solusi yang bersifat instrumental, yaitu; penyediaan buku ajar, buku-buku referensi, dan daftar referensi mata kuliah; dan (2) solusi yang bersifat psikis/mental, yaitu membangun kesadaran mahasiswa tentang pentingnya membangun cara berpikir ilmiah, sikap, dan karakter yang mulya dalam kehidupan sehari-hari termasuk dalam proses pembelajaran.Kata kunci: karakter, pembelajaran, struktur mental, teknologi informasi